A new species of Manoa Fittkau (Diptera: Chironomidae), with DNA barcodes from Xianju National Park, Oriental China - Qi, Xin; Wang, Xin-Hua; Andersen, Trond; Lin, Xiao-Long (Zootaxa, 2017)
The genus Manoa and the tribe Pseudochironomini are recorded from the Oriental region for the first time. Manoa xianjuensis Qi & Lin sp. n. from Xianju National Park, Zhejiang, China is described and illustrated as adult male and female, the latter associated with the male by standard DNA barcodes. A neighbor joining tree based on available Pseudochironomini DNA barcodes and keys to the adults in Manoa are given.